2013
DOI: 10.1016/j.aller.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of morphine, pholcodine and poppy seed IgE assays in drug-abusers and allergic people

Abstract: Opiates may be significant allergens. Drug-abusers and people sensitised to tobacco are at risk. Both the prick and specific IgE tests efficiently detected sensitisation to opiates. The highest levels were related to more-severe clinical profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
5
1
5
Order By: Relevance
“…Finally, unlike Armentia et al. , we do not endorse the use of sIgE antibodies to poppy seed as a marker to document genuine opiate allergy. First, the currently available poppy seed assay uses an aqueous extract that is prepared from native allergens and contains highly cross‐reactive components and epitopes, such as CCD and ubiquitous pan allergens such as profilins and ns‐LTP that might severely hamper correct diagnosis of opiate allergy .…”
Section: Cns Depressants (Cannabis Opioids and Kava)contrasting
confidence: 90%
“…Finally, unlike Armentia et al. , we do not endorse the use of sIgE antibodies to poppy seed as a marker to document genuine opiate allergy. First, the currently available poppy seed assay uses an aqueous extract that is prepared from native allergens and contains highly cross‐reactive components and epitopes, such as CCD and ubiquitous pan allergens such as profilins and ns‐LTP that might severely hamper correct diagnosis of opiate allergy .…”
Section: Cns Depressants (Cannabis Opioids and Kava)contrasting
confidence: 90%
“…Los niveles más altos de IgE específi ca se relacionan con cuadros clínicos más severos. 51 La prueba de IgE específi ca a las semillas de amapola tiene una sensibilidad de 82.6 % y una especifi cidad de 100 %. 4 Otro método diagnóstico es la IgE sérica específi ca para el fármaco.…”
Section: Diagnósticounclassified
“…39 Se puede utilizar la prueba ImmunoCAP para el amonio cuaternario de la morfi na e ImmunoCAP para alérgenos de la folcodina. 51 Las pruebas cutáneas por escarifi cación detectan efi cientemente la sensibilización a los opiáceos. Se puede realizar una prueba cutánea con un extracto de semillas de opio (Papaver somniferum), que tiene una sensibilidad de 64.2 % y una especifi cidad de 98.4 %, mayor que las pruebas de morfi na, la codeína y rocuronio para ver la sensibilidad a los opiáceos.…”
Section: Diagnósticounclassified
See 1 more Smart Citation
“…Modern research has shown that PPCE acts by modulating pain signaling pathways in the central nervous system. Varieties of pharmacological effects of PPCE have been found according to the previous studies, such as sedation, anti-tussive, and anti-diarrheal [2][3][4]. Among the chemical components of PPCE, isoquinoline alkaloids such as morphine (MPE) and codeine (CON) have been demonstrated to be the main and dominant active compounds [5,6].…”
Section: Introductionmentioning
confidence: 99%